Agent-Oriented Information Systems IV - Kolp, M. (Springer, 2017)
This is the eighth year that the Agent-Oriented Information Systems (AOIS) workshops have been held. Papers submitted to AOIS show an increase in quality and maturity as agent technology is being increasingly seen as a viable alternative for software and systems development. In AOIS, we focus on the application of agent technology in information systems development and explore the potential for facilitating the increased usage of agent technology in the creation of information systems in the widest sense. This year’s workshops were held in conjunction with two major, international computing research conferences: the first, in May 2006, was affiliated with the AAMAS conference in Hakadote, Japan and chaired by Garcia, Ghose and Kolp. The second was held in conjunction with the international CAiSE conference held in Luxembourg (June 2006) and chaired by Bresciani, Henderson-Sellers and Mouratidis. (Details of all preceding workshops are to be found at http:// www. aois. org. ) The best papers from both these meetings were identified and authors invited to revise and extend their papers in light of the reviewers’ comments and feedback at the workshop. Following submission to this compendium volume, another round of reviews was undertaken resulting in what you can read here. These re-reviews were undertaken by three members of the Programme Committee – we wish to thank both the authors for undertaking the necessary revisions and the reviewers for this extra call on their precious time.